READING FICTION FOR BETTER LIFE IN LUIS SEPULVEDA’S THE OLD MAN WHO READ LOVE STORIES - Melania Priska Mendrofa (UIN Alauddin Makassar, 2020)
Reading is therapeutic. This statement reflects reading as a technique to heal people’s mental problems and increase self-ability. Researches prove that reading is not only for entertainment, but also a tool to solve problem in people’s life. Meanwhile, the question comes up in the term of what kind of book suggested to read. In Luis Sepulveda’s The Old Man Who Read Love Stories, it is implied that reading fiction helps the old man, Antonio, to deal with his old age and loneliness. Reading a love story enlightens the old man’s mind and feelings. Life is overloaded by complex problems, such as war, poverty, gender problem, and nature destruction. People become sentimental to life; there is no happy ending story in life, only death. Meanwhile, Sepulveda sees fiction as the rescuer for a problematic life. This paper will discuss why people read fiction and the effects of reading fiction for someone’s life. The positive impacts of reading fiction for mental health and self-transformation are supposed to encourage people to start a new habit of reading for a better life.